Multiview Shooting Geometry for Multiscopic Rendering with Controlled Distortion - J. Prévoteau; S. Chalençon-Piotin; D. Debons; L. Lucas; Y. Remion (International Journal of Digital Multimedia Broadcasting)
A fundamental element of stereoscopic and/or autostereoscopic image production is the geometrical analysis of the shooting and viewing conditions in order to obtain a qualitative 3D perception experience. This paper firstly compares the perceived depth with the shot scene depth from the viewing and shooting geometries for a couple of shooting and rendering devices. This yields a depth distortion model whose parameters are expressed from the geometrical characteristics of shooting and rendering devices. Secondly, these expressions are inverted in order to design convenient shooting layouts yielding chosen distortions on specific rendering devices. Thirdly, this design scheme provides three shooting technologies (3D computer graphics software, photo rail, and camera box system) producing qualitative 3D content for various kinds of scenes (real or virtual, still or animated), complying with any prechosen distortion when rendered on any specific multiscopic technology or device formerly specified.